Exploring Reimbursement Pathways for Lifestyle Medicine and Health Promotion Services in Occupational Therapy. - Sadek, Amy; Billock, Christy; Jordan, Katie (American Journal of Occupational Therapy)
Occupational therapy practitioners are uniquely qualified and positioned to offer both preventive and rehabilitative models of care. However, the status quo of current reimbursement models has created a barrier to occupational therapy practitioners receiving adequate reimbursement, if any, for doing health promotion and lifestyle-focused work. In this Health Policy Perspectives article, we emphasize the need for reimbursement and propose pathways for new and perhaps untapped or underutilized models of reimbursement for occupational therapy practitioners. These pathways require education and advocacy efforts to showcase our distinct value as key reimbursable and interdisciplinary players in lifestyle medicine and health promotion work. In this Health Policy Perspectives article, we emphasize the need for reimbursement and propose pathways for new and perhaps untapped or underutilized models of reimbursement for occupational therapy practitioners.